Dashboard Monitoring Website Dosen Studi Kasus Universitas Bina Darma - Iqbal Wahyudi; Ahmad Syazili (Jurnal Pengembangan Sistem Informasi dan Informatika, 2021)
The concept of dashboard performance is an information system application model provided for managers to present performance quality information, from a company or organizational institution, dashboards have been widely adopted by companies or businesses. In this study, the authors designed a dashboard that was used as a monitoring system for lecturer posting activities at Binadarma University, Palembang. The limitation of the dashboard in this study only displays data based on lecturer posts which will be developed in the form of a website. Dashboard design is more effective and efficient than viewing data manually, which requires managers to open a database to view data one by one from lecturers' posts. In making the lecturer website dashboard, the data taken is in the form of posting data stored in the lecturer database, the data that has been taken will be presented in the dashboard in the form of graphs, tables and dashboards.